[POSITIF: à ajouter ?|The Social Construction of Female Sexuality in a Sexualized Work Environment (SWE): The Case of a Comedy Club - Philaretou, Andreas G.; Young, Christi L. (Sexual Addiction & Compulsivity, 2007)
This qualitative investigation seeks to identify the sociocultural determinants and psychoemotional ramifications of essentialist gender scripting on female employees in a sexualized work environment (SWE), such as a comedy club. Sexualized work environments incorporate work and sexuality and exist on a continuum according to the frequency and intensity of the sexual economic exchange that takes place within them. In this study, interviews were conducted with 13 female employees at a comedy club in Southwest Michigan to explore the social construction of female sexuality in such an environment.
Publisher: Routledge _eprint: https://doi.org/10.1080/10720160601150139
Keywords: Sophie-Anne